Vanessa Bell and Virginia Woolf: an Artist and a Critic? - Liliane Louvel (Cahiers Victoriens et Edouardiens)
This paper will delve further into an aspect related to the ‘sisters’ arts’ I have already only hinted at, that of the relation between discourse and the image. That of the supposed discourse of the image, and of the so-called ‘reticence’ of painting or of its silence as acknowledged by Woolf. Therefore, a particular light will be cast on this aspect thanks to the embodied ‘sisters’ arts’, helping me to prolong my reflection on both topics. The issue of the ‘trans-lation’ of one art into another medium, will be coupled with the phenomenon of what happens when an artist is a critic and a critic an artist. This time, this article will examine the issue from a point of view opposite to the commonly adopted one, that is, it will not examine only what Virginia wrote about painting in her essays, in her letters or in her novels, but first and foremost what Vanessa had to say about painting and literature in the short volume, Sketches in Pen and Ink prefaced by her daughter, which contains most of her essays.